Re/Writing the center: approaches to supporting graduate students in the writing center - Lawrence, Susan, editor; Zawacki, Terry Myers, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
How core writing center pedagogies and institutional arrangements are complicated by the need to create intentional, targeted support for advanced graduate writers. Most writing center tutors are undergraduates, whose lack of familiarity with the genres, preparatory knowledge, and research processes integral to graduate-level writing leaves them underprepared.--Provided by publisher.
Rethinking the WAC/writing center/graduate student connection / Michael Pemberton -- The rise of the graduate-focused writing center: exigencies and responses / Sarah Summers -- On the distinct needs of multilingual STEM graduate students in writing centers / Steve Simpson -- Getting the writing right: writing/language centres and issues of pedagogy, responsibility, ethics, and international English in graduate student research writing / Joan Turner -- Intake and orientation: the role of initial writing center consultations with graduate students / Patrick S. Lawrence, Molly Tetreault, and Thomas Deans -- Hybrid consultations for graduate students: how pre-reading can help address graduate students' needs / Elena Kallestinova -- "Noticing" language in the writing center: preparing writing center tutors to support graduate multilingual writers / Michelle Cox -- "Novelty moves": training tutors to engage with technical content / Juliann Reineke, Mary Glavan, Doug Phillips, and Joanna Wolfe -- A change for the better: writing center/WID partnerships to support graduate writing / Laura Brady, Nathalie Singh-Corcoran, and James Holsinger -- "Find something you know you can believe in": the effect of dissertation retreats on graduate students' identities as writers / Ashly Bender Smith, Tika Lamsal, Barrie Olson, Adam Robinson, and Bronwyn Williams -- More than dissertation support: aligning programs with professional development and other doctoral student needs / Marilyn Gray -- Revisiting the remedial framework: how writing centers can better serve graduate students and themselves / Elizabeth Lenaghan.
Keywords: Writing centers; Graduate students; English language -- Rhetoric -- Study and teaching (Higher); Academic writing -- Study and teaching (Higher); Tutors and tutoring